MEMAHAMI NIAT BELI KONSUMEN DALAM MEMBELI PRODUK MINUMAN ROOTBEER MENURUT TEORI PERILAKU YANG TERENCANAKAN (TPB) - Herry Suwito, 1242020105 (Jurnal Mahasiswa Pasca Sarjana, 2015)
World sales and marketing is a very dynamic world, where so many strategies and triktrik used to attract consumers to buy a product. World beverage itself, in particular carbonated beverages, has tersediri challenges, ranging from the shift of the community of beverages Health Soft drink to drink, the number of competitors who compete with a variety of promotions and discounts. However, not all discounts and promotions done on a large scale can bind a large enough number of consumers. Greatness of a brand or product is not necessarily offset by higher sales of these products. This has led researchers to conduct behavioral research, menggunakkan theory of planned behavior of Prof. Ijek Ajzen to see the influence of attitudes, norms, and control of the consumers purchase intention. The respondents of this study amounted to 150 people with the status of visitors Indomaret Point at Jl. And Jl Pemuda Semarang. Pandanaran Semarang. The sampling technique using proportional random sampling, and multiple regression analysis techniques using Statistical Product and Service Solutions (SPSS). The results showed that attitudes, norms and Control Behavior positive and significant effect on intention. Marketing managerial implications of this research are the benefits to be received (attitude), support or encouragement from the surrounding community (the norm), but does not depend on the ability to purchase and availability of products in the existing outlet2. By sharing experiences, consumers can encourage other consumers to participate purchase Rootbeer beverage products. When we return to the description of the respondents, it can be seen that the majority of respondents (70%) polled rensponden is male, aged 26-32 yr (46.7%) with the highest level of education is high school (64.7%). Appropriate marketing strategy for this consumer group, can increase the intentions and behavior of consumers into buying products Rootbeer drink. This consumer group is actually a target consumer segment Rootbeer beverage products. Managerial marketing should conduct an evaluation to improve marketing rootbeer. Keywords: Theory Of Planned Behavior, Attitude Towards The Behavior, Subyektif Norm, Percieved Behavior Control, Intentions